Flaps versus skin grafts in neovagina creation for vaginal agenesis - Ulaganathan, Prabhakar (International Surgery Journal, 2020)
Background: Women with congenital uterovaginal agenesis have normal development of all secondary sexual characteristics. They face the cruel fact of being unable to bear children and enjoy sexual satisfaction. Good neo vaginal reconstruction is important in improving functional and psycho social impacts to womanhood. The aim of the study was to compare the three commonly done surgical procedures for vaginal reconstruction. Methods: All the vaginal agenesis patients who attended Department of plastic surgery Madras Medical College, Chennai during the period from August 2004 to April 2007 were included in our study. Results: In Abbe McIndoe procedure, graft take was full in all 7 cases with good cosmetic appearance. Flaps survived in all 10 patients underwent pudendal thigh flap surgery. 2 patients underwent horse shoe shaped labia minora flaps. The cosmetic appearance was fair because of the distortion of the labia. The mean vaginal depth obtained was 8 cm and width was 2 cm. Conclusions: Cosmetic appearance was good in patients who underwent McIndoe procedure as the genitalia were not distorted. Contracture rate was more in patients who underwent McIndoe procedure especially who were irregular in using stents. Flap procedure especially pudendal thigh flaps which has the least contraction rate is the preferable treatment option for such patients.